Cross-cultural adaptation and psychometric validation of the Persian version of the central sensitization inventory. (February 2021) - Noorollahzadeh, Karim; Kahrizi, Sedigheh; Fesharaki, Mohammad Gholami; Heidarian, Majid; Neblett, Randy; Behzadipour, Saeed
Abstract: Background: The Central Sensitization Inventory (CSI) is a patient-reported tool to assess symptoms associated with central sensitization (CS). It consists of two parts: Part A assesses 25 somatic and emotional CS-related health symptoms, and part B asks if one has previously been diagnosed with a list of 10 Central Sensitivity Syndromes and related conditions. Objectives: The aim of this study was to translate and cross-culturally adapt the CSI into Persian and to evaluate its psychometric properties. Design: Cross-sectional study. Method: After completing the Persian translation, the psychometric properties of the Persian CSI (CSI-Per) were evaluated in 256 patients with chronic pain and 46 healthy subjects. Results: A confirmatory factor analysis confirmed a 1-factor model suggested in a large recent comprehensive multicountry study. Test-retest reliability (ICC = 0.934; P < 0.001) and the internal consistency (Cronbach's α = 0.87) were both good. After dividing the patient subjects into severity level subgroups, based on CSI-Per total scores, significant associations were found with the Persian version of the pain catastrophizing scale, pain duration, current pain intensity, maximum, minimum and average pain intensity in the past week and average pain intensity in the past month. In addition, total CSI-Per scores differentiated between patients and healthy subjects. Conclusion: The CSI-Per demonstrated good validity and reliability to assess symptoms associated with CS in Persian-speaking patients with chronic pain. Highlights: The results offer support for the reliability and validity of the CSI-Per. The study confirmed a 1-factor model suggested in a large recent multicountry study. Total CSI-Per scores could differentiate between patients and healthy subjects.